2012
DOI: 10.3997/1873-0604.2012009
|View full text |Cite
|
Sign up to set email alerts
|

Coupled hydrogeophysical inversion of electrical resistances and inflow measurements for topsoil hydraulic properties under constant head infiltration

Abstract: Accurate estimation of topsoil hydraulic properties is important for understanding water flow and solute transport in the vadose zone. Coupled hydrogeophysical inversion schemes that enable the use of multiple geophysical and hydrological data for the estimation of soil hydraulic properties have recently been proposed. In these coupled inversion schemes, a hydrological model describing the process under investigation is coupled to a forward geophysical model and hydraulic parameters are directly estimated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 78 publications
1
29
0
Order By: Relevance
“…Mualem (1976) reported that λ equal to 0.5 was an optimal value for a data set of 45 disturbed and undisturbed samples. In many studies aiming to estimate the soil hydraulic properties from coupled hydrogeophysical inversion the parameter λ is fixed to 0.5 to minimize the number of unknowns, e.g., Looms et al (2008); Hinnell et al (2010); Huisman et al (2010); Mboh et al (2011, 2012a,b). Given these considerations, we assumed θ r , θ s , and λ to be known in the hydrogeophysical inversion process.…”
Section: Methodsmentioning
confidence: 99%
“…Mualem (1976) reported that λ equal to 0.5 was an optimal value for a data set of 45 disturbed and undisturbed samples. In many studies aiming to estimate the soil hydraulic properties from coupled hydrogeophysical inversion the parameter λ is fixed to 0.5 to minimize the number of unknowns, e.g., Looms et al (2008); Hinnell et al (2010); Huisman et al (2010); Mboh et al (2011, 2012a,b). Given these considerations, we assumed θ r , θ s , and λ to be known in the hydrogeophysical inversion process.…”
Section: Methodsmentioning
confidence: 99%
“…Looms et al [2008] showed that five layers were needed to explain their field data, but that only permeability and one additional fitting parameter could be retrieved for each layer. Hinnell et al [2010] and Mboh et al [2012a] investigated how surface-based ERT monitoring of infiltration tests could improve soil hydraulic property estimation. Hinnell et al [2010] showed in a synthetic example that petrophysical coupling can reduce parameter errors, but only if the conceptual hydraulic model is correct.…”
Section: Cassiani and Binley [2005] Inverted For Soil Hydraulic Propementioning
confidence: 99%
“…Considering an undisturbed soil core, Mboh et al [2012a] also improved their parameter estimates when combining inflow measurements with ERT data-. They also highlighted the challenge of assigning appropriate weights to each data set in the objective function.…”
Section: Cassiani and Binley [2005] Inverted For Soil Hydraulic Propementioning
confidence: 99%
“…[]; Mboh et al . []. A number of different approaches to model the saturation dependency of the coupling are proposed in the literature [ Guichet et al ., ; Revil and Cerepi , ; Linde et al ., ; Allègre et al ., ; Jougnot et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The approach of Linde et al . [] was confirmed by independent experiments [ Mboh et al ., ]. Jougnot et al .…”
Section: Introductionmentioning
confidence: 99%